NaOH/PEG-400: An eloquent system for the synthesis of new thienyl benzo[b]1,4-diazepines - Mandawad, Gajanan Gopinath; Shaikh, Baseer Mubeen; Chobe, Santosh Subhash; Konda, Shankaraiah Guruvaiah (European Journal of Chemistry, 2020)
A simple and eloquent procedure for the synthesis of a new series of thienyl benzo[b]1,4-diazepines is reported. They were synthesized by the condensation of o-phenylenediamine (o-PDA) with distinct hetero chalcones using NaOH in polyethylene glycol (PEG-400) as green and alternative reaction solvent. The significances of this present method are shorter reaction time, easy work-up, high yields, and mild reaction conditions. Furthermore, this method is environment friendly and without use of an expensive catalyst. The all newly synthesized compounds are characterized by the spectroscopic methods.